2019
DOI: 10.1128/jvi.01162-19
|View full text |Cite
|
Sign up to set email alerts
|

Limited Intrahost Diversity and Background Evolution Accompany 40 Years of Canine Parvovirus Host Adaptation and Spread

Abstract: Canine parvovirus (CPV) is a highly successful pathogen that has sustained pandemic circulation in dogs for more than 40 years. Here, integrating full-genome and deep-sequencing analyses, structural information, and in vitro experimentation, we describe the macro- and microscale features that accompany CPV’s evolutionary success. Despite 40 years of viral evolution, all CPV variants are more than ∼99% identical in nucleotide sequence, with only a limited number (<40) of substitutions becoming fixed or wides… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 75 publications
10
75
0
1
Order By: Relevance
“…The “Asian CPV-2c” has progressively become the dominant strain in several areas of Asia within a few years from its first identification [ 18 ], and at the same time it has also reached Europe and Africa [ 19 , 20 , 22 ]. Many of the mutations observed in CPV are short-lived and both parallel evolution and reversion are commonplace for this virus [ 10 ]. However, as CPV-2c with VP2 amino acid residues 5Gly, 267Tyr, 324Ile and 370Arg was never reported before 2013 and it has been frequently detected since then, it can be assumed that a virus with this distinctive amino acid profile is progressively expanding its spread in the world dog population, continuing to acquire mutations such as the amino acid change Ala→Gly in residue 5 [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “Asian CPV-2c” has progressively become the dominant strain in several areas of Asia within a few years from its first identification [ 18 ], and at the same time it has also reached Europe and Africa [ 19 , 20 , 22 ]. Many of the mutations observed in CPV are short-lived and both parallel evolution and reversion are commonplace for this virus [ 10 ]. However, as CPV-2c with VP2 amino acid residues 5Gly, 267Tyr, 324Ile and 370Arg was never reported before 2013 and it has been frequently detected since then, it can be assumed that a virus with this distinctive amino acid profile is progressively expanding its spread in the world dog population, continuing to acquire mutations such as the amino acid change Ala→Gly in residue 5 [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CPV antigenic variants replicate and spread more effectively in susceptible hosts, gaining the ability to infect cats [ 8 , 9 ]. The detection of other amino acid changes in the VP2 protein and the poor phylogenetic resolution supporting the three variants are leading to a progressive move away from the use of the CPV-2a, CPV-2b and CPV-2c terminology towards the use of the defining amino acid substitutions for each of these antigenic variants [ 10 ]. Nevertheless, references to the traditional nomenclature are prevalent in the literature and adopted herein.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mutations in this site may have antigenic significance and affect the host immune response. This mutation was estimated to have multiple evolutionary origins [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…These amino acid changes lead to the difference in two neutralizing antigenic sites on the surface of viral capsid (Allison et al., 2016; Hoelzer & Parrish, 2010; Stucker et al., 2012). Up‐to‐date, it is clearly showed that CPV‐2a spreads worldwide and is the key ancestor for the later variants, designated as CPV‐2b, CPV‐2c or new CPV‐2a, which are distributed variably (Voorhees et al., 2020). Current epidemiological surveys show that the CPV‐2a variant predominantly circulates in most Asia and in European countries while the CPV‐2b variant is a major antigenic variant in Iceland, the UK, the USA, Africa and some Asian countries (Clark et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…After its emergence, CPV‐2c became widely distributed in other European and Latin American countries (Zhou, Zeng, Zhang, & Li, 2017). In recent years, CPV‐2c has spread many geographic regions and currently causes fatal disease in both domestic and wild dog populations (Aldaz et al., 2013; Decaro & Buonavoglia, 2012; Geng et al., 2015; Parthiban, Mukhopadhyay, Antony, & Pillai, 2010; Voorhees et al., 2020).…”
Section: Introductionmentioning
confidence: 99%